Checklists of Fish Species Infected with Parasites of the Genera Lamproglena and Pseudolamproglena (Copepoda: Cyclopoida: Lernaeidae) in Iraq - Mhaisen, Furhan; Ali, Atheer; Adday, Thamir (Iraqi Journal of Aquaculture, 2024)
A total of 51 references dealing with the occurrence of species of the genera Lamproglena and Pseudolamproglena infecting fish species in Iraq, until mid-2024 were consulted. A total of 22 fish species were found to be infected with two species of the genus Lamproglena (L. chinensis and L. pulchella) and two species of the genus Pseudolamproglena (P. annulata and P. boxshalli), in addition to some unidentified species of the genus Lamproglena. L. chinensis was recorded from two fish species, L. pulchella from 20 fish species, P. annulata from 12 fish species, P. boxshalli from five fish species and unspecified Lamproglena sp. from one fish species. Such parasites were recorded from their fish hosts from different water bodies (rivers, canals, lakes, marshes and drainage networks) as well as from some fishponds. Apart from Cyprinion kais and Garra variabilis, all the remaining fish species were infected with L. pulchella, and/ or other parasite species, with the maximum number of four parasite species was recorded only from Leuciscus vorax.